Assessment of Credit Support to Small and Medium-Sized Businesses in the Republic of Kazakhstan - Talimova, Lyazat A.; Kalkabaeva, Gauhar M. (Journal of Advanced Research in Law and Economics, 2016)
This article presents the analysis of a current state of bank crediting of small and medium-sized business in Kazakhstan. Credit interaction of a banking system of Kazakhstan and subjects of business is characterized by insufficiently full use of opportunities of crediting. As a result of the research, the main problems existing in modern credit relationship of banks and businesses were revealed, such as low availability of the bank credits, high interest rate for the credits, long terms and complexity of giving and consideration of credit demands, especially in regions, high concentration of credit risks in the sphere of business, absence or a lack of mortgage providing, low availability and quality of information on credit products, and limitation of their volume. The low share of bank loans in structure of financing sources of small and medium-sized enterprises testifies to low motivation of executives to take the credits on the current conditions. Besides, structural weakness of small and medium-sized business sector and decrease in its contribution to GDP growth becomes one of the factors of concentration increase of credit risk in banks’ loan portfolio. The article considers state programs on support and development of business, and offers measures to increase their efficiency. Despite a large number of institutes of financial support, the share of the acting subjects’ coverage of small and medium-sized enterprises is insignificantly small. Both state and banks prove the need in realization of measures on further development of bank crediting.